A waveguide thermal emitter - Marcel W. Pruessner; Steven T. Lipkowitz; Jacob N. Bouchard; Nathan F. Tyndall; Scott A. Holmstrom; Gerald L. Leake Jr.; Tat Ngai; Kyle J. Walsh; Peter G. Goetz; Todd H. Stievater (APL Photonics)
Light sources monolithically integrated with optical filters, modulators, and detectors are necessary components for photonic systems on a chip. For broadband applications such as chemical or biological sensing using absorption spectroscopy, white light sources are preferred over lasers or amplified spontaneous emission sources. In particular, thermal sources offer a straightforward means for broadband optical emission. However, to date, there have been few reports of waveguide-coupled thermal sources. In this work, we demonstrate a suspended nanophotonic waveguide-coupled broadband thermal source. It is heated by an adjacent resistive heater that permits temperatures in excess of 1000 °C at electrical powers of tens of milliwatts. We measure the waveguide-coupled emission, confirming broadband operation from 875 to 1600 nm (instrumentation limited). Thermal simulations show good agreement with measurements, and optical modeling accurately describes the heater–waveguide coupling and polarization.